Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.5 - Integrated Review - Summary on Rational Expressions - Page 527: 22


equation $x=-7/3$

Work Step by Step

$\frac{9}{x^2-4}+\frac{2}{x+2}=\frac{-1}{x-2}$ $\frac{9}{(x+2)(x-2)}+\frac{2}{x+2}=\frac{-1}{x-2}$ $(x-2)(x+2)*\frac{9}{(x+2)(x-2)}+(x-2)(x+2)*\frac{2}{x+2}=(x-2)(x+2)*\frac{-1}{x-2}$ $9+2(x-2)=-1*(x+2)$ $9+2x-4=-x-2$ $5+2x=-x-2$ $3x+7=0$ $3x=-7$ $3x/3=-7/3$ $x=-7/3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.